Prevalence of dental caries and treatment needs among school going children of Chandigarh - Prabakar, Jayashri; John, Joseph; Srisakthi, D (Indian journal of dental research, 2016)
Introduction: Dental caries is the most common chronic disease of childhood that interferes with normal nutrition intake, speech, and daily routine activities. Dental caries is a lifetime disease, and the highest priority risk group is school children. Aim: To assess the prevalence of dental caries and treatment needs among school going children of Chandigarh. Materials and Methods: A cross-sectional study was done among school going children of Chandigarh in the age group of 3-17 years. The subjects were selected from four randomly selected schools. All the children from the selected schools were examined. A total of 4493 subjects formed the sample size. Dentition status was assessed using dft index by Gruebbel for primary dentition and DMFT index by Klein, Palmer, Knutson for permanent dentition, respectively. Chi-square test was used to find an association between the study variables. Independent t-test and one-way ANOVA were used to compare the mean difference. Results: Among the 4493 study subjects, caries prevalence was found to be 47.3%. Mean dft and DMFT score of the population was 1.06 ± 1.995 and 0.41 ± 1.022, respectively. When analyzing the treatment needs among various age groups 42.6% of the study subjects required oral prophylaxis and 45% required restorative procedures. Conclusion: Based on the findings, it can be concluded that high prevalence of caries was found in primary dentition than permanent dentition and most of the decayed teeth were untreated. This study emphasize the need for treating dental caries at its earliest possible stage and parents should be made aware of caries preventive measures for their children.